Visible Spectrophotometric Method for the Estimation of Clebopride in Pure and in Pharmaceutical Formulations - Kalaichelvi, R.; Jayachandran, E. (Asian Journal of Chemistry, 2012)
A simple, sensitive, accurate and economic method has been developed for the quantitative estimation of clebopride in pure and in tablets. This method is based on the reaction of the drug in methanolic solution with p-dimethylamino benzaldehyde in acidic condition producing Schiff's base having a lmax at 444 nm. Beer's law is obeyed in concentrations ranging from 50-175 μg/mL. The results of analysis have been validated statistically and by recovery studies.